What do health workers think about a population exposed to health inequalities? The Bastogi case. (13th November 2019) - Salvatori, L M; Tofani, M; Angelozzi, A; Caminada, S; Paglione, L; Iorio, S; Ricotta, G; Brandimarte, A M; Biliotti, D; Marceca, M
Abstract: Introduction: Previous qualitative researches highlighted that people living in Bastogi - a peripheric area of Rome marked by social deprivation - have difficulties in accessing and relating health services. We explored the healthcare workers' perception of the relationship with such population. Methods: A 42 items questionnaire was addressed to the reference Local Health Unit employees, evaluating: context knowledge; perception of the relationship between users and health services and between users and operators; training needs. The association between answers and social characteristics of the respondents has been evaluated through Chi Square Test for categorical variables and T Student Test for continuous variables. Results: Questionnaire respondents were 73 (50% of the total employees). 77% reported knowing Bastogi. Adverse social determinants mostly identified (>65%) were economic problems, housing conditions and unemployment, while less people pointed out the poor social support network (38%). 50% assumed that Bastogi inhabitants face health inequalities. 26% claimed to have difficulties in the relationship with users; 81% considered useful a training activity about the relationship with socioeconomic deprived users. 25% believed the responsibility for the main social problems in Bastogi lies in the inhabitants themselves. Such answer was statistically more frequent among: administrative professionals, professionals with longer length of service, those who deny the existence of health inequalities and those who don't feel the need of training. Further results will be presented during the congress. Conclusions: Preliminary results of the survey confirm that the relationship between users from a socially deprived area and the competent services is problematic, and underline the need for training of healthcare professionals on the subject. This need is also perceived by the majority of the respondent personnel. Key messages: We explored the healthcare workers' perception of the relationship they have with a population exposed to health inequalities. Interventions and trainings will be implemented to contain this problem.